2010
DOI: 10.7589/0090-3558-46.1.218
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the Brush-Tailed Rock-Wallaby (Petrogale Penicillata)

Abstract: The brush-tailed rock-wallaby (Petrogale penicillata) is listed as vulnerable on the International Union for Conservation of Nature (IUCN) Red List of Threatened Species. Parasitic diseases have been proposed as possible contributing factors to the decline of the species, but very little is known about the effects of parasites on this host. This study determined the antibody prevalence of the protist Toxoplasma gondii in a wild brush-tailed rock-wallaby population from three neighboring colonies in southeast Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this study, we found that of 16 macropod marsupials of three different species inhabiting a defined geographic area in the arid rangelands of Western Australia, all were infected. This is much greater than the prevalence found in three serological studies on macropods in different areas of Australia; 8.5% among Macropus rufogriseus and Thylogale billardierii in Tasmania [22], 15.5% and among Macropus fuliginosus in south western Australia [23] and 5% among Petrogale penicillata in southeast Queensland [24]. This suggests the need for serological studies on a larger sample of macropods from our study site, to determine whether our results are really reflective of a higher prevalence of T. gondii in this region.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, we found that of 16 macropod marsupials of three different species inhabiting a defined geographic area in the arid rangelands of Western Australia, all were infected. This is much greater than the prevalence found in three serological studies on macropods in different areas of Australia; 8.5% among Macropus rufogriseus and Thylogale billardierii in Tasmania [22], 15.5% and among Macropus fuliginosus in south western Australia [23] and 5% among Petrogale penicillata in southeast Queensland [24]. This suggests the need for serological studies on a larger sample of macropods from our study site, to determine whether our results are really reflective of a higher prevalence of T. gondii in this region.…”
Section: Discussionmentioning
confidence: 58%
“…Toxoplasma gondii antibodies (MAT, 1:40) were detected in 3 out of 64 (4.6%) brush-tailed rock wallaby in Queensland, Australia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For terrestrial mammals, extensive descriptions of lesions and diseases attributed to parasite presence are available and some parasites are even considered to regulate host populations (e.g. Gulland 1992, Nettles et al 2002, Barnes et al 2010). Much less is known about parasites in marine mammals (Lehnert et al 2010) and existing studies have con-centrated primarily on parasite taxonomy (Dougherty 1949, Arnold & Gaskin 1975 or directly parasiterelated pathology (Dailey & Stroud 1978, Faulkner et al 1998, Jepson et al 2000.…”
Section: Introductionmentioning
confidence: 99%